Equids’ Core Vaccines Guidelines in North America: Considerations and Prospective - Hélène Desanti-Consoli; Juliette Bouillon; Ronan J. J. Chapuis (Vaccines, 2022)
Vaccination against infectious diseases is a cornerstone of veterinary medicine in the prevention of disease transmission, illness severity, and often death in animals. In North American equine medicine, equine vaccines protecting against tetanus, rabies, Eastern and Western equine encephalomyelitis, and West Nile are core vaccines as these have been classified as having a heightened risk of mortality, infectiousness, and endemic status. Some guidelines differ from the label of vaccines, to improve the protection of patients or to decrease the unnecessary administration to reduce potential side effects. In North America, resources for the equine practitioners are available on the American Association of Equine Practitioners (AAEP) website. Conversely, in small companion animals, peer review materials are regularly published in open access journals to guide the vaccination of dogs and cats. The aims of this review are to present how the vaccine guidelines have been established for small companion animals and horses in North America, to review the equine literature to solidify or contrast the current AAEP guidelines of core vaccines, and to suggest future research directions in the equine vaccine field considering small companion animal strategies and the current available resources in equine literature.